HUBUNGAN ANTARA NAFSU MAKAN DENGAN ASUPAN ENERGI DAN PROTEIN PADA PASIEN KANKER PAYUDARA POST KEMOTERAPI[Correlation between Appetite with Energy and Protein Intake of Post Chemotherapy Breast Cancer Patients] - Silviana Putri; Merryana Adriani; Yayuk Estuningsih (Media Gizi Indonesia, 2019)
Chemotherapy drugs used to kill or inhibit proliferation of cancer cell that are cytotoxic and causing side effect for breast cancer patients. The side effect of chemotherapy drugs is decreasing the appetite which causing decrease in energy and protein intake, and could affect nutritional status. This study aim to determine the relationship between appetite with energy and protein intake of post chemotherapy breast cancer patients. This research was an analytic observational research using cross sectional design and purposive sampling conducted at Dr. Ramelan Navy Hospital Surabaya with a sample size of 50 patients. Correlation between appetite with energy and protein intake were analyzed using Pearson correlation. The average of energy and protein intake were 976.3±304.2 kcal and 29.4±12.9 g. Pearson correlation test showed signifi cant correlation between appetite as chemoteraphy side effect with energy intake (p=0.000; r=-0.558) and protein intake (p=0.000; r=-0.504). Decreasing of appetite due to chemoterapy reduce the energy and protein intake of breast cancer patient. Patient are suggest to consume foods in small portion but often to maintain adequate energy and protein intake.